Distinct Gene Expression Patterns of Ion Channels and Cytokines in Rat Primary Sensory Neurons During Development of Bone Cancer and Cancer Pain - Zhai, Mingzhu; Yang, Shaomin; Lin, Simin; Zhu, Hanxu; Xu, Lihong; Liao, Huabao; Song, Xue-Jun (Frontiers in Molecular Neuroscience, 2021)
Abstract Cancer and cancer pain processes a major clinical challenge and the underlined mechanisms of pathogenesis remain elusive. We examined the specific changes in the transcriptomic profiles in the dorsal root ganglion (DRG) neurons of rats with bone cancer and bone cancer pain (BCP) using RNA sequencing technology. The bone cancer and BCP was induced by tumor cells implantation (TCI) into the tibia bone cavity in adult female rats. One day after treatment, TCI caused up- and down-regulation of thousands of genes in DRG. These genes were mainly involved in the immune process, inflammatory response, and intracellular signaling transduction of carbohydrate and cytokine. The cAMP and calcium signaling pathways were the major processes in the initial responses. Differentially expressed gene (DEG) analysis further showed that the genes for ion channels increased during day 1-7, while the genes for cytokine signaling pathways sustainedly increased during day 1-14 after TCI. The time courses of gene expression for ion channels and cytokines support their distinct roles in the early induction and late maintenance of BCP development. In addition, among the top 500 up- and down-regulated genes, 80-90% were unique for bone cancer pain as well as neuropathic and inflammatory pain, while less than 2% were shared among the three different forms of pain. This study reveals the uniqueness of mechanisms underlying bone cancer with pain, which is, to a large extent, differently from pain after acute inflammatory and nerve injury and provides novel potential targets of DEGs for bone cancer with pain.